Frequency Of Urinary Tract Infections in Protein-Calorie Malnutrition Children in Mardan Medical Complex: UTI Frequency in Malnourished Children at Mardan - Khalid, Shah; Hussain, Ansar; Kiramatullah , .; Sardar, Hamza; Khan, Abdul Basit; Kalsoom, Rizwana (Pakistan Journal of Health Sciences, 2025)
Protein-calorie malnutrition (PCM) remains a significant cause of morbidity and mortality in low- and middle-income countries, where it often coexists with infections such as urinary tract infections (UTIs). Malnourished children are immunologically vulnerable, and UTIs further complicate their clinical course. Objectives: To determine the frequency of UTIs and associated risk factors among children with PCM admitted to a tertiary care hospital in Mardan, Pakistan. Methods: This descriptive cross-sectional study was conducted in the Department of Pediatrics, Mardan Medical Complex, from August 2024 to January 2025. A total of 123 children aged 6 months to 12 years with PCM were included. Demographic, clinical, and laboratory data were collected using a structured proforma. Urinary investigations included microscopy, dipstick nitrite test, and culture. Associations between UTI and clinical-demographic variables were analyzed using the Chi-square test, with effect size reported by Cramer’s V. Results: The prevalence of UTI was 48.0%. Significant associations were observed with age <24 months (p<0.001, V=0.642), rural residence (p=0.035, V=0.190), severe acute malnutrition (p=0.015, V=0.219), and edema (p=0.017, V=0.216). Escherichia coli (30.1%) was the most common pathogen isolated. Most children improved with treatment (89.4%), though complications such as sepsis (10.6%) and acute kidney injury (6.5%) were reported. Conclusions: UTIs are common among malnourished children, particularly those under 2 years, severely malnourished, or from rural areas. Early screening and targeted interventions may reduce morbidity and improve outcomes.